(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Field studies were conducted in the Department of Biological Control Techniques / Technical College of Al-Mussaib during the Period 2016-2017, Using different concentration of extracts for Allium stivum and Coriandrum sativum to control the Varroa destructor as well as a survey of Varroa destructor in different areas of Babylon province . The results showed that Varroa destructor was found in high density and different frequency in areas reached to 89% in Alkawther and less infection 32% is Alnile. the extract of Coriandrum sativum high signification rate for killing 75.33% at 100% conc. While the lest rate 12.11 at 25% conc. The result showed that Alliwm sativum has high rate in killing rate reached to 83% at 100% conc. while the killing rate reached at 34.3 at 25% concentration .